Recognizing and reducing corruption risks in land management in Vietnam (Hà Nội, 2011)
The book analyzes and explains the cause of corruption in land administration and the existing types of corruption
Keywords: Land use,Real estate development,Sử dụng đất,Quản lý bất động sản; Corrupt practices,Tham nhũng